Saussure’s Concept in Interpreting Features of the New Testament Text - Vdovichenko Andrei (Вестник Православного Свято-Тихоновского гуманитарного университета: Сериа III. Филология)
In the article is regarded the use of Saussure’s opposition «language - speech» in explaining features of the NT linguistic data. The concept of the dichotomy leads to an incorrect interpretation of the NT writers’ communicative activity.